Effects of psychological empowerment on organizational commitment, role ambiguity and managerial performance in an environment of low budget participation - Friedrich, Marcos Paulo; Zonatto, Vinicius Costa Da Silva; Lavarda, Carlos Eduardo Facin; Lunardi, Micheli Aparecida (Advances in Scientific and Applied Accounting, 2023)
Objective: To analyze the effects of psychological empowerment on organizational commitment, role ambiguity and managerial performance in an environment of low budget participation. Method: A descriptive survey with a questionnaire and quantitative data analysis (path analysis) was carried out with a non-randomized sample of 183 mid-level managers who work as general managers and administrative managers in a state-owned financial institution in southern Brazil. Results: The results revealed a positive influence of psychological empowerment on organizational commitment and managerial performance, however, a negative influence is perceived between empowerment and role ambiguity. The findings also reveal that organizational commitment has a positive relationship with managerial performance. The evidence found allows us to conclude that in specific contexts of low budget participation, psychological empowerment can increase managerial performance by increasing organizational commitment and reducing role ambiguity. It was found that the greater the organizational commitment, the greater the effects of psychological empowerment on managerial performance. Contribution: The environment of low budget participation is characterized as a context in which mid-level managers do not have the authority to define objectives and goals, as well as in the budget preparation process. In this context, this study contributes to the understanding of the psychological and behavioral effects on managerial performance in low budget participation environments, indicating to senior managers of state entities the behavioral effects perceived by mid-level managers as a result of the budget configuration adopted.